Rhizosphere priming: a nutrient perspective - Dijkstra, Feike A.; Carrillo, Yolima; Pendall, Elise; Morgan, Jack A. (Frontiers in Microbiology, 2013)
Rhizosphere priming is the change in decomposition of soil organic matter (SOM) caused by root activity. Rhizosphere priming plays a crucial role in soil carbon (C) dynamics and their response to global climate change. Rhizosphere priming may be affected by soil nutrient availability, but rhizosphere priming itself can also affect nutrient supply to plants. These interactive effects may be of particular relevance in understanding the sustained increase in plant growth and nutrient supply in response to a rise in atmospheric CO2 concentration. We examined how these interactions were affected by elevated CO2 in two similar semiarid grassland field studies. We found that an increase in rhizosphere priming enhanced the release of nitrogen (N) through decomposition of a larger fraction of SOM in one study, but not in the other. We postulate that rhizosphere priming may enhance N supply to plants in systems that are N limited, but that rhizosphere priming may not occur in systems that are phosphorus (P) limited. Under P limitation, rhizodeposition may be used for mobilisation of P, rather than for decomposition of SOM. Therefore, with increasing atmospheric CO2 concentrations, rhizosphere priming may play a larger role in affecting C sequestration in N poor than in P poor soils.